Izydor z Sewilli, Synonimy: tematyka, styl, źródła dzieła - Krynicka, Tatiana (Vox Patrum, 2018)
The article is devoted to the Synonyma – one of the most interesting writings of Isidore of Seville (560-636). The author briefly presents its content, structure, style, writes about its influence on medieval Latin prose and about its antecedents, both classical as well as Christian (biblical and liturgical).